Adorno's 'addendum'. (October 2017) - Jaffe, Aaron
Adorno's 'addendum' names the experience by which socially constrained agents are jolted into resistance against their suffering. The impulse to action is simultaneously intra-mental and somatic, and thus forms the locus of a jointly conscious and bodily impetus to confronting the ideological and material forces that produce contemporary unfreedom. In this way the 'addendum' is a historically developing, indeterminate, yet inexhaustible glimmer of hope for both agents and theorists who make social suffering central to their critical analysis. This article explores the structure of the addendum by unpacking its presentation first in Negative Dialectics and then by way of the one-sided and cautionary illustrations of Buridan's ass and Hamlet in the History and Freedom lectures. While aesthetic, ideal, affect-centered and Freudian interpretations of the addendum have been developed, appreciating the somatic or bodily, the intra-mental or conscious, and the historicized accounts of nature and reason that Adorno weaves together to explain ever-present possibilities of resistance requires instead a non-reductive materialist and dialectical lens.